A Ferroptosis-Related Gene Model Predicts Prognosis and Immune Microenvironment for Cutaneous Melanoma - Xu, Congcong; Chen, Hao (Frontiers in Genetics, 2021)
Background Cutaneous melanoma is a common but aggressive tumor. Ferroptosis is a recently discovered cell death with important roles in tumor biology. Nevertheless, the prognostic power of ferroptosis-linked genes remained unclear in cutaneous melanoma. Methods Cutaneous melanoma patients of TCGA (The Cancer Genome Atlas) were taken as the training cohort, while GSE65904 and GSE22153 as validation cohorts. Multi-factor Cox regression model was used to build a prognostic model, and the performance of model was assessed. Functional enrichment and immune infiltration analysis were used to clarify the mechanisms. Results A five ferroptosis-linked gene predictive model was developed. ALOX5 and GCH were illustrated as independent predictive factors. Functional assessment showed enriched immune-linked cascades. Immune infiltrating analysis exhibited the distinct immune microenvironment. Conclusion Herein, a novel ferroptosis-related gene prognostic model was built in cutaneous melanoma. This model could be used for prognostic prediction, and maybe helpful for the targeted and immunotherapies.